Hubungan Antara Parent And Peer Attachment Terhadap Nilai Ujian Akhir Blok (UAB) Ilmu Kedokteran Komunitas Pada Mahasiswa Angkatan 2015 Fakultas Kedokteran Universitas Lampung: Hubungan Antara Parent And Peer Attachment Terhadap Nilai Ujian Akhir Blok (UAB) Ilmu Kedokteran Komunitas Pada Mahasiswa Angkatan 2015 Fakultas Kedokteran Universitas Lampung - heidy putri gumandang; Dwita Oktaria; Anisa Nuraisa Djausal (Medula, 2022)
Learning achievement is the end of result that is awaited in learning something and there are several factors that influence it, one of it is environment. The family environment consisting of economic conditions, the atmosphere of house, and parents are mentioned have a role in learning achievement. When someone is in a family or community environment, students do not escape from social situations such as peers. The aim is to find out the relationship between parent and peer attachment with the result of Community Medicine (IKKOM) block in Medical Student, Faculty of Medicine, University of Lampung. The study used a cross sectional design and conducted in October 2018. Subjects were 183 students of batch 2015, Faculty of Medicine, University of Lampung. The results were analyzed using the Fisher and Chi-square test. This study used 183 respondents who showed that the level of attachment to parents of medical student batch 2015 Lampung University was high security, which was a percentage of 93.44% and the level of attachment to friends of medical student batch 2015 Lampung University was high security a percentage of 86.34%. Furthermore, the bivariate test obtained p value> 0.05, which means that statistically there is no significant relationship between parent and peer attachment with the result of Community Medicine (IKKOM) block in Medical Student, Faculty of Medicine, University of Lampung.We concluded that there was no significant relationship between parent and peer attachment with the result of Community Medicine block in Medical Student of 2015, Faculty of Medicine, University of Lampung.